2018
DOI: 10.22159/ajpcr.2018.v11i11.24922
|View full text |Cite
|
Sign up to set email alerts
|

Yellow Pitaya (Hylocereus Megalanthus) Fatty Acids Composition From Ecuadorian Amazonia

Abstract: Objective: The aim of this study was to determine the composition of methyl esters fatty acids (FAMEs) in yellow pitaya (Hylocereus megalanthus) seeds cultivated in the Palora, Ecuador Amazonian region.Methods: Yellow pitaya oil was obtained from yellow pitaya seeds using the Soxhlet technique. FAMEs identification and quantification were carried out using the gas chromatography (GC) with mass spectrometry (MS) and the database Library NIST14.L to identify the FAMEs present in yellow pitaya oil.Results: Yellow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…They were classified initially under the genus Cereus, but the genus Hylocereus (synonym of Selenicereus) is currently used (The Plant List, 2013). Further, morphological and genetic heterogeneity in pitahaya by hybridization among species and varieties caused taxonomical confusion to identify them at the species level (Abirami et al, 2021). Daza et al (2014) reported 102±1.2, 77.6±0.4 and 202.7±1.1 mg GAE g -1 of dry sample, of peel, pulp and seeds, respectively.…”
Section: Total Phenolic Contentmentioning
confidence: 99%
“…They were classified initially under the genus Cereus, but the genus Hylocereus (synonym of Selenicereus) is currently used (The Plant List, 2013). Further, morphological and genetic heterogeneity in pitahaya by hybridization among species and varieties caused taxonomical confusion to identify them at the species level (Abirami et al, 2021). Daza et al (2014) reported 102±1.2, 77.6±0.4 and 202.7±1.1 mg GAE g -1 of dry sample, of peel, pulp and seeds, respectively.…”
Section: Total Phenolic Contentmentioning
confidence: 99%